Serum IgG Anti-Toxoplasma gondii Antibody Concentrations Do Not Correlate Nested PCR Results in Blood Donors - Nakashima, Fabiana; Pardo, Valquíria Sousa; Miola, Marcos Paulo; Murata, Fernando Henrique Antunes; Paduan, Natalia; Longo, Stefani Miqueline; Brandão de Mattos, Cinara Cássia; Pereira-Chioccola, Vera Lucia; Ricci, Octávio; de Mattos, Luiz Carlos (Frontiers in Cellular and Infection Microbiology, 2020)
Background:Toxoplasma gondii infects millions of individuals worldwide. This protozoan is food and water-borne transmitted but blood transfusion and organ transplantation constitute alternative forms for transmission. However, the influence of IgG anti-T. gondii antibodies in molecular analysis carried out in peripheral blood still remain unclear. This study aimed to investigate the serum IgG anti-T. gondii antibody concentrations correlate Nested PCR results in blood donors. Methods: 750 blood donors were enrolled. IgM and IgG anti-T. gondii antibodies were assessed by ELISA (DiaSorin, Italy). Nested PCR was performed with primers JW62/JW63 (288 bp) and B22/B23 (115 bp) of the T. gondii B1 gene. The mean values of IgG concentration were compared for PCR positive and PCR Negative blood donors using the t-test or Mann-Whitney according to the normal distribution (p-value ≤ 0.05). Results: 361 (48.1%) blood donors presented positive serology as follow: IgM+/IgG−: 5 (0.6%); IgM+/IgG+: 21 (2.8%); IgM−/IgG+: 335 (44.7%) and 389 (51.9%), negative serology. From 353 blood donors with positive serology tested, the Nested PCR was positive in 38 (10.8%) and negative in 315 (89.2%). There were no differences statistically significant between the mean values of serum IgG anti-T. gondii antibody concentrations and the Nested PCR results. Conclusions: In conclusion, our data show that variations in the serum IgG anti-T. gondii antibody concentrations do not correlate T. gondii parasitemia detected by Nested PCR in chronically infected healthy blood donors.